2021
DOI: 10.3389/fimmu.2021.702733
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of CCR9+ T Helper Cells From Primary Sjögren’s Syndrome Patients Identifies CCL5 as a Novel Effector Molecule

Abstract: IntroductionCCR9+ Tfh-like pathogenic T helper (Th) cells are elevated in patients with primary Sjögren’s syndrome (pSS) and indicated to play a role in pSS immunopathology. Here we delineate the CCR9+ Th cell-specific transcriptome to study the molecular dysregulation of these cells in pSS patients.MethodsCCR9+, CXCR5+ and CCR9-CXCR5- Th cells from blood of 7 healthy controls (HC) and 7 pSS patients were FACS sorted and RNA sequencing was performed. Computational analysis was used to identify differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…Although CCR9+ effector CD8 T cells expressed the highest CCL5 levels, also in all other CD27/CD45RO-defined CD8 T cell subsets a significantly higher CCL5 expression was found in CCR9+ cells as compared to CCR9- CD8 T cells, which we previously also demonstrated for CD4 T cells ( 17 ). Since CCR9 is a chemokine receptor that initiates migration of T cells towards CCL25 under both physiological and inflammatory conditions and CCL5 is a chemokine that recruits several types of leukocytes to inflamed sites, the high expression of CCL5 in CCR9-expressing cells indicates that facilitating recruitment of other inflammatory cells is a main feature of these cells in immunopathology.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Although CCR9+ effector CD8 T cells expressed the highest CCL5 levels, also in all other CD27/CD45RO-defined CD8 T cell subsets a significantly higher CCL5 expression was found in CCR9+ cells as compared to CCR9- CD8 T cells, which we previously also demonstrated for CD4 T cells ( 17 ). Since CCR9 is a chemokine receptor that initiates migration of T cells towards CCL25 under both physiological and inflammatory conditions and CCL5 is a chemokine that recruits several types of leukocytes to inflamed sites, the high expression of CCL5 in CCR9-expressing cells indicates that facilitating recruitment of other inflammatory cells is a main feature of these cells in immunopathology.…”
Section: Discussionsupporting
confidence: 79%
“…Earlier work in our group has shown that CCR9+CXCR5- “Tfh-like” CD4 T cells form a distinct group of cells, which show a potent pro-inflammatory phenotype and have an increased frequency in peripheral blood and salivary gland tissue of pSS patients ( 15 ). Chemokine CCL5 was identified as a potential target, and was highest expressed by effector CCR9+ CD4 T cells ( 17 ). CD8 T cells, however, are described as a more potent producer of CCL5 ( 36 , 37 ): a finding we confirmed in this study for both HC and pSS patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations